Investigation of Indoor and Outdoor Air Quality at Elementary Schools in Hanoi, Vietnam - Anh Le, Hoang; Quynh Linh, Vu Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 1DO - 10.25073/2588-1094/vnuees.4550, 2020)
Indoor air quality is having insufficient attention despite its importance for human health, especially for schools because children is one of the most sensitive groups to air pollution. This study focuses on monitoring the air quality inside classrooms at some elementary schools (ELS) of Hanoi with representative parameters including PM 2.5 , PM 10 , CO 2 , NO 2 , and VOCs. Simultaneously, those parameters in school yards are also monitored to provide data for comparison and evidence of the sources of indoor pollution. The results indicated that the main air quality issue in schools is particulate matters, particularly PM 2.5 . It also showed that schools locating near traffic roads have concentrations of 2 - 3 times higher than standards. VOCs concentration levels are high indoor and in school yards located near markets and traffic roads. CO 2 and NO 2 indoor concentrations are below standards in all schools. The ELS-7 has most of indoor and in yards concentrations at the highest values. Two significant factors effecting air quality of schools are traffic and activities of residential areas around them. Keywords: Indoor air quality, School, Vietnam.